TEMA CINTA DALAM NOVEL SHIOSAI KARYA MISHIMA YUKIO - Fadli, Zaki Ainul; Hastuti, Nur (Universitas Diponegoro, 2017)
This paper is titled Theme of Love in Mishima Yukio’s Shiosai. The purpose of writing is to reveal the major themes in Mishima Yukio's Shiosai and its relationship to other structures, especially figures and characters, plots and backgrounds. The analysis uses structural methods that have the concept that in a building of a literary work consists of interrelated and inseparable structures. The results of this paper indicate that the theme of love is a major theme that is evidenced by the correlation and relationship of love problems with other structures, especially figures and characterizations, plot, and background. <a href=